2013
DOI: 10.1038/nrn3538
|View full text |Cite
|
Sign up to set email alerts
|

Hypnotic suggestion: opportunities for cognitive neuroscience

Abstract: Hypnosis uses the powerful effects of attention and suggestion to produce, modify and enhance a broad range of subjectively compelling experiences and behaviours. For more than a century, hypnotic suggestion has been used successfully as an adjunctive procedure to treat a wide range of clinical conditions. More recently, hypnosis has attracted a growing interest from a cognitive neuroscience perspective. Recent studies using hypnotic suggestion show how manipulating subjective awareness in the laboratory can p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
152
0
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(178 citation statements)
references
References 104 publications
7
152
0
10
Order By: Relevance
“…In the normal awake state, we identified a negative correlation between external and internal awareness in healthy volunteers: explicit subjective reports for increased intensity of internal awareness were related to increased connectivity in the DMN, whereas increased external awareness scores were associated with increased connectivity in the external network [64]. Under hypnosis, the external network exhibited reduced functional connectivity, whereas the DMN showed reduced connectivity in its posterior midline and parahippocampal structures but increased connectivity in its lateral parietal and middle frontal areas [12], while other works showed opposite results with increased activity in posterior regions of the DMN as compared to decreased metabolic activity in anterior DMN areas [36,46]. Other fMRI studies have shown a hypnosis-related reduction in DMN connectivity [10,39], and increased activity in lateral prefrontal regions (involved in attentional/extrinsic systems) [10].…”
Section: Hypnosis In the Brain ''At Rest'' Fmri And Pet Studiesmentioning
confidence: 60%
See 2 more Smart Citations
“…In the normal awake state, we identified a negative correlation between external and internal awareness in healthy volunteers: explicit subjective reports for increased intensity of internal awareness were related to increased connectivity in the DMN, whereas increased external awareness scores were associated with increased connectivity in the external network [64]. Under hypnosis, the external network exhibited reduced functional connectivity, whereas the DMN showed reduced connectivity in its posterior midline and parahippocampal structures but increased connectivity in its lateral parietal and middle frontal areas [12], while other works showed opposite results with increased activity in posterior regions of the DMN as compared to decreased metabolic activity in anterior DMN areas [36,46]. Other fMRI studies have shown a hypnosis-related reduction in DMN connectivity [10,39], and increased activity in lateral prefrontal regions (involved in attentional/extrinsic systems) [10].…”
Section: Hypnosis In the Brain ''At Rest'' Fmri And Pet Studiesmentioning
confidence: 60%
“…Finally, while we cannot clearly conclude that conversion disorders and hypnotically suggested conversion symptoms share strictly the same neuropsychological processes, studies nevertheless suggest many parallels between the features of clinical conversion symptoms and hypnosis. Hypnosis can be considered as a useful analogue for creating conversion and dissociation symptoms in healthy subjects, by the generation and easy termination of clinically similar experiences in laboratory conditions [46].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, considerable attention has been devoted to the possibility of using hypnosis to model different psychological and neurological phenomena (Oakley & Halligan, 2009, 2013 , and motor paralysis (Cojan et al, 2009). The value of such research is closely tied to the assumption that HS individuals respond to hypnotic suggestions through uniform mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Hypnosis is able to alter the phenomenological properties of participants' subjective experience (Kihlstrom, 2013;Oakley and Halligan, 2013). The process of hypnosis can be divided into induction and suggestion stages.…”
Section: Introductionmentioning
confidence: 99%